Analysis of Risk Factors Influencing the Incidence of Diabetes Mellitus among Employees - Ira Puspa Rachmawati; Irfansyah Baharuddin Pakki (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disorder that remains a major public health concern globally. Its prevalence is influenced by various lifestyle and hereditary factors. This study aims to analyze the risk factors contributing to the incidence of DM among employees at Segiri Community Health Center. A retrospective case-control study was conducted using secondary data from health screenings and fitness assessments of Segiri Community Health Center employees in September 2023. From 50 staff members, 40 with complete records were included: 10 DM cases and 30 non-DM controls (1:3 ratio). Data included medical history, lifestyle behaviors, and anthropometric measurements. Analysis involved univariate and bivariate tests using cross-tabulation and Odds Ratio (OR). The most significant risk factor was abnormal Body Mass Index (BMI), as all DM cases had abnormal BMI values. Other influential factors included parental history of diabetes (OR = 18.0), personal history of hypertension (OR = 9.3), and parental history of hypertension (OR = 6.0). Additional contributing factors were low fruit and vegetable intake (OR = 4.0), excessive salt intake (OR = 1.63), and abnormal waist circumference (OR = 1.31). Smoking and alcohol consumption were not significantly associated with DM in this sample. Abnormal BMI and a family history of diabetes and hypertension significantly contribute to the incidence of DM. Targeted interventions focusing on these modifiable and non-modifiable risk factors are essential for effective workplace prevention strategies.